Fenomena dan Realitas Sistem Pelayanan Publik Berbasis E-Government di Kota Batu - Aprianus Oematan; Cahyo Sasmito; Cakti Indra Gunawan (Jurnal Syntax Admiration, 2024)
This research was conducted from May to August 2018 at the Batu City Communication and Information Office. The number of informants in this study was 6 (six) people, including people who use the Batu City BATT information system. The research method used is a qualitative descriptive approach with data collection techniques used is the Milles and Huberman model which asks open interview questions with informants and refers to grand theories. The data inspection technique used is data triangulation. The results showed that the implementation of the BATT information system was appropriate to support the government's performance in realizing fast, precise, efficient services and to manage existing resources and encourage the Government in developing the BATT information system as an E-government-based system and is a mandate from the central government to each regional government in developing their regions by building an electronic-based government system (E-government) to improve services and accelerate the management of existing resources for mutual prosperity and progress.